WHAT SHAPES CITIZENS' EVALUATIONS OF THEIR PUBLIC OFFICIALS' ACCOUNTABILITY? EVIDENCE FROM LOCAL ETHIOPIA. (21st August 2013) - Jilke, Sebastian
SUMMARY In this article, we study which institutional factors shape citizens' views of the local accountability of their public officials. Our departing assumption is that evaluations of local accountability reflect not only citizens' poltical attitudes and beliefs but also whether local institutions contribute to an environment of mutual trust, accountability and ultimately democratic legitimacy. Combining public opinion data from a large‐N citizen survey (N = 10 651) with contextual information for 63 local governments in Ethiopia, we look at access to information, participatory planning and the publicness of basic services as potential predictors of citizens' evaluations of local public officials. Our findings suggest that local context matters. Jurisdictions that provide access to information on political decision making are perceived to have more accountable officials. Moreover, when local governments provide public fora that facilitate citizens' stakes in local planning processes, it positively affects citizens' evaluations of the accountability of their officials. Our study adds to the empirical literatrure by showing that establishing local institutions that can foster citizen–government relations at the local level through inclusive processes is crucial for improving public perceptions of accountability. Copyright © 2013 John Wiley & Sons, Ltd.